CRUSTAL ACCRETION ALONG THE NORTHERN MID ATLANTIC RIDGE (52°-57°N): PRELIMINARY RESULTS FROM EXPEDITION V53 OF R/V AKADEMIK SERGEY VAVILOV - Skolotnev S. G.; Sanfilippo A.; Peyve A. A.; Palmiotto C.; Ivanenko A. N.; Cuffaro M.; Veklich I. A.; Muccini F.; Ponomarenko E. P.; Petracchini L.; Kuleshov D. A.; Basch V.; et al. (Edizioni ETS, 2023)
This study investigates crustal accretion processes along the northern stretch of the Mid-Atlantic Ridge (MAR) between the Charlie Gibbs (52°-53°N) and Bight (57°N) transforms. These long-lived transform systems, active for more than 40 Ma, bound a ~ 550 km-long MAR segment influenced to the South by the Azores and to the North by the Iceland mantle plumes. The Bight transform is located at the tip of the Reykjanes Ridge, where the spreading direction, influenced by the southward propagation of the Iceland plume, changes from oblique (30° to the axis) to perpendicular to the axis. Four hundred kilometres to the south, the MAR is offset by the Charlie Gibbs transform system consisting of two long-lived right-lateral transform faults linked by a short ~ 40 km-long spreading segment. Previous expeditions surveyed large areas of these two transform systems, defining their main morphological features. Based on these bathymetric data, Expedition V53 of the R/V A.S. Vavilov carried out an intense dredging program coupled with magnetic surveys in an area spanning from 57° to 52°N, covering both the Bight and the Charlie Gibbs transform systems. We collected 1850 kg of rock samples including limestones, basalts, gabbros and mantle peridotites from 27 dredging sites, along with two 6-m long sedimentary cores. The sampled lithologies are globally in agreement with the contrasting morphological features of the two transform faults. We discuss here and compare the geology of these two major transform systems and assess the influence of the Icelandic plume on seafloor morphology at the Bight Fracture Zone.